2018
DOI: 10.1128/jvi.02016-17
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Human-Type Receptor Binding by Ferret-Transmissible H5N1 with a K193T Mutation

Abstract: All human influenza pandemics have originated from avian influenza viruses. Although multiple changes are needed for an avian virus to be able to transmit between humans, binding to human-type receptors is essential. Several research groups have reported mutations in H5N1 viruses that exhibit specificity for human-type receptors and promote respiratory droplet transmission between ferrets. Upon detailed analysis, we have found that these mutants exhibit significant differences in fine receptor specificity comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…While rescuing this virus again, we found that a large majority of the viruses contained a second mutation, T160A. This T160A mutation results in the loss of an N-glycosylation site in the head of HA that has been implicated to be important in receptor binding and specificity for H5 HA (de Vries et al, 2014; Paulson and de Vries, 2013; Peng et al, 2018). We therefore analyzed H5 wild-type versus H5 Y161A and H5 T160A Y161A for replication efficiency in Mardin Darby canine kidney (MDCK) cells.…”
Section: Resultsmentioning
confidence: 94%
“…While rescuing this virus again, we found that a large majority of the viruses contained a second mutation, T160A. This T160A mutation results in the loss of an N-glycosylation site in the head of HA that has been implicated to be important in receptor binding and specificity for H5 HA (de Vries et al, 2014; Paulson and de Vries, 2013; Peng et al, 2018). We therefore analyzed H5 wild-type versus H5 Y161A and H5 T160A Y161A for replication efficiency in Mardin Darby canine kidney (MDCK) cells.…”
Section: Resultsmentioning
confidence: 94%
“…The switch in specificity from the α2,3 to the α2,6 Sia linkage seems to be a requirement for efficient human-to-human transmission [ 30 ]. A third receptor-associated inter-host difference is the length and branching of the glycan, and the number of Sia that are displayed [ 32 , 33 ]. This may affect the binding of HA to the receptor as more branched and multi-Sia glycans can bind virus with higher affinity.…”
Section: Influenza a Virus Spillover And Epidemic Emergencementioning
confidence: 99%
“…Though, numerous substitutions were also identified that are associated with a binding preference for α2,3 receptors (S2d Table). The well-known Q222L and G224S substitutions associated with increased binding to α2,6 receptors and decreased α2,3 binding were not observed [55,56].…”
Section: Resultsmentioning
confidence: 99%